Analisis Potensi Reduksi Sampah oleh Pemulung di Tempat Pengelolaan Sampah Terpadu Bantargebang - Putri, Billie Juan; Sari, Gina Lova (Universitas Batanghari Jambi, 2024)
Indonesia is the country with the fourth largest population in the world. In 2022, waste in Indonesia reached 36.00 million tons/year. DKI Jakarta Province has a vast waste generation rate of 3.10 million tons/year potentially ending in a waste processing site called TPST Bantargebang. The DKI Jakarta Province recorded as much as 7,000 to 8,000 tons/day of waste entering the TPST Bantargebang, with a regional waste reduction target of 27.00%. TPST Bantargebang has reduced waste by processing waste into fuel and electricity. Another reduction factor that has yet to receive attention is the role of waste pickers. In 2022, the number of waste pickers at TPTS Bantagebang is 6,413 people. This research examines the potential role of waste pickers in reducing waste at the TPST Bantargebang. This research is an observational study conducted by sampling and interviewing the waste pickers. The sample in this research was 98 waste pickers who collected waste samples for eight consecutive days. The results show that waste pickers at TPST Bantargebang potentially reduced 144.08 kg of waste/person/day, with the most prominent composition being plastic waste at 49.88%. Based on these results, it can be concluded that scavengers at TPST Bantargebang can reduce waste by up to 12.55%. The value of potential waste reduction by waste pickers can be used for waste reduction calculations at TPST Bantargebang.